CHARACTERISTICS OF PROFESSIONAL TRAINING OF GYMNASTICS COACHES - Raisa N. Teryokhina; Elena N. Medvedeva; Elena S. Kryuchek; Irina A. Viner-Usmanova (Высшее образование в России)
Quantitative and qualitative characteristics of coaches are the essential indicators of possibilities for preparing highly qualified gymnasts in the country. Our country is proud of a great number of outstanding coaches, who glorified rhythmic gymnastics as a sport. Many National Federations invite Russian coaches and this promotes developing rhythmic gymnastics in the world, testifies the effectiveness of the training system, and enhances coaches' qualification in rhythmic gymnastics in Russia. The high quality of gymnastics coaching is provided by education in special educational establishments and also qualification development by means of assimilating and mastering of the previous experience of the leading coaches in the country and all over the world. Coach preparation should be led by paying special attention to the demands of the contemporary sports practice with the consideration of the future.